Multifunctional Coding Metasurface With Left and Right Circularly Polarized and Multiple Beams - Li, Sijia; Li, Zhuoyue; Han, Bowen; Huang, Guoshuai; Liu, Xiaobin; Yang, Huanhuan; Cao, Xiangyu (Frontiers in Materials, 2022)
In this paper, a multifunctional coding metasurface (MCMS) has been proposed to realize the dual-circularly polarized beams and the beam focusing with transmission and reflection. The phase of transmitted circular polarized wave is controlled by rotating the elements of metasurface, and the corresponding element with Pancharatnam-Berry (PB) phase is provided for the metasurface. The phase distribution of circular polarized quad-beam is designed according to the convolution theorem of patterns and the phase compensation principle. In order to validate the proposed metasurface, the multifunctional meta-device is fabricated and measured to illustrate the quad-beam with left circular polarization in the transmissive space and the right circularly polarized quad-beam in the reflective space. The experimental results agree with the simulated data substantially. The MCMS has the potential applications in wireless communications due to the features of low profile, compact, and lightweight.